2018
DOI: 10.1371/journal.pone.0192135
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan oligosaccharide ameliorates acute lung injury induced by blast injury through the DDAH1/ADMA pathway

Abstract: ObjectiveTo investigate the protective effect of chitosan oligosaccharide (COS) on acute lung injury (ALI) caused by blast injury, and explore possible molecular mechanisms.MethodsA mouse model of blast injury-induced ALI was established using a self-made explosive device. Thirty mice were randomly assigned to control, ALI and ALI + COS groups. An eight-channel physiological monitor was used to determine the mouse physiological index. Enzyme linked immunosorbent assay was used to measure serum inflammatory fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…; Liu et al. ), and DDAH1 upregulation has been associated with tumor regression in a xenograft mouse model (Yung et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Liu et al. ), and DDAH1 upregulation has been associated with tumor regression in a xenograft mouse model (Yung et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial DDAH1-specific knockout mice have impaired angiogenesis (Zhang et al 2013;Dowsett et al 2015). DDAH1/ADMA/NOS pathway regulation of caspase-3 mediated apoptosis has been described (Wang et al 2016;Hou et al 2018;Liu et al 2018), and DDAH1 upregulation has been associated with tumor regression in a xenograft mouse model (Yung et al 2016). Caspase-3, in addition to its central role in apoptosis, is paradoxically known to enhance cellular growth (Laplante et al 2010;Li et al 2010;Kennedy et al 2014;Feng et al 2015), and to promote angiogenesis (Povero et al 2013;Feng et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Y.‐E. Liu et al () reported that caspase‐3 is a key enzyme that mediates apoptosis. Activated caspase‐3 degrades Bcl‐2 protein to prevent its antiapoptotic effect however, once caspase‐3 is activated, the occurrence of apoptosis is irreversible…”
Section: Discussionmentioning
confidence: 99%
“…A precise model of lung blast injury was used as previously described [10]. Brie y, mice were anesthetized by abdominally injecting 2% pentobarbital sodium (1.5 ml/kg).…”
Section: Blast-exposure Induced Lung Injurymentioning
confidence: 99%
“…Subsequently, intrapulmonary hemorrhage further causes the formation of free radicals, edema, accumulation of in ammatory factors and oxidative damage, which may develop into acute respiratory distress syndrome [9][10][11][12][13]. Our previous studies found that blast injury caused a signi cant increased expression of interleukin-1 (IL-1β), IL-6 and tumor necrosis factor (TNF-α), a signi cant decreased expression of IL-10, an increase in Evans blue leakage, and an signi cant increase in in ammatory cell in ltration [14][15][16]. In addition, we have previously reported that blast exposure-induced in ammation in the lungs occurred within the rst 12-48 h and peaked at approximately 24 h [17].…”
mentioning
confidence: 99%